Research into the themes covered in Pandita Jamyangarav’s compilation of sources from the time of the Mongol khans - Dashlkhagvaa, Ganbold; Ulamsuren, Tsetsegdari; Saaya, Oyumaa M. (The New Research of Tuva, 2025)
This article analyzes the content of the work “The Lineage of the Mongol Khans in Mongolian Texts” written in the late 19th / early 20th centuries by Pandita Jamyangarav (1867–1918), a Mongolian monk, poet, philosopher and scholar. This work provides valuable source materials for Mongolian history and an account of the khans of the Golden lineage of Mongolia. It contains interesting stories and information unrecorded in previous historical accounts and is of particular interest because it was written in Tibetan. It is also a valuable source for the history of the spread of Buddhism in Mongolia.The history of Mongolia is remarkable because it was transmitted mainly orally rather than through writing. As a result, stories and oral traditions always add to the historical material that is passed down through the scriptures. However, very few Mongolian historical texts have been written in the Tibetan language. It is distinguished by the language’s shortened writing.Although this text, or one bearing a similar name, is mentioned in some lists of Pandita Jamyangarav’s works, it includes valuable materials which is introduced in the context of Mongolian culture and history for the first time. It has been translated into Mongolian, its textual and scribal errors have been rectified, and it has been made available for scholarly analysis.
Keywords: lama; Tibetan language; Pandita Jamyangarav; Mongols; Buddhism; seal of Genghis Khan; Buddhist teacher